ANALISIS TINGKAT RESILIENSI MATEMATIS SISWA PADA PEMBELAJARAN MATEMATIKA - Ulhasna, Nadya; Rahmi, Depriwana; Kurniati, Annisah; Yuniati, Suci (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The purpose of this study is to determine the resilience level of 11th-grade students at MA PP Assalam Naga Beralih in mathematics, as mathematical resilience is crucial for students to be able to withstand challenges in learning mathematics. This research employs a quantitative approach combined with descriptive methodology. The population in this study consists of 11th-grade students at MA PP Assalam Naga Beralih. The sample of this study includes fifteen 11th-grade students from MA PP Assalam Naga Beralih. The research instrument used is a non-test instrument in the form of a questionnaire. The research data is derived from the mathematical resilience questionnaire. The percentages were examined and explained as part of the data analysis method. The results of the study show that 27% or 4 students fall into the high category, 60% or 9 students fall into the medium category, and 13% or 2 students fall into the low category. Therefore, it can be concluded that the mathematical resilience level of 11th-grade students at MA PP Assalam Naga Beralih, based on the percentage of responses from each student according to the indicators, indicates a medium level of resilience